Adhesive composition and thermally fusible member including the same
Patent Information
- Application Number
- JP2023130893
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-21
Smart Images

Figure 2025025780000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive composition and a heat-sealable member and a packaging material for electricity storage devices using the same, which can be used in various industrial product fields such as the electrical field, automotive field, and industrial field, and belong to these technical fields. [Background technology]
[0002] Acid-modified polyolefins obtained by grafting an organic acid having an unsaturated double bond onto a polyolefin with low polarity have an acid-modified moiety with high polarity and a polymer backbone with low polarity. For this reason, acid-modified polyolefins are used as a surface treatment agent when coating polyolefin resins such as polypropylene, which have traditionally been considered to be poorly adhesive resins, and as a raw material for adhesives for bonding polyolefins together or polyolefins to polar materials such as metals.
[0003] The typical battery packaging material used for laminated batteries has a three-layer structure with aluminum foil at the center, and adhesive is used between each layer. The three layers are the base layer that will be the outside of the battery after the laminated battery is formed, the barrier layer made of aluminum foil or stainless steel foil that prevents the penetration of moisture and air, and the sealant layer that insulates the barrier layer from contacting the electrodes and electrolyte and heat-seals the outer periphery to bond them together, and each layer may be formed of two or more layers. Of these, the sealant layer that comes into contact with the electrolyte is made of an olefin-based film such as polypropylene film, and a polyurethane-based adhesive made by crosslinking acid-modified polymers such as acid-modified polyolefins and acid-modified styrene-based elastomers with an isocyanate-based crosslinking agent is used to bond it to the aluminum foil.
[0004] Among them, an adhesive composed of an acid-modified polyolefin and an isocyanate-based crosslinking agent has been widely used in recent years because it can obtain high adhesive strength. For example, Patent Documents 1 and 2 describe a packaging material for a battery case in which a thermoplastic resin unstretched film layer and an aluminum foil layer are bonded via an adhesive layer containing a polyolefin resin having a carboxyl group and a polyfunctional isocyanate compound. As described in Patent Documents 1 and 2, such an adhesive composed of an acid-modified polyolefin and an isocyanate-based crosslinking agent is mainly used as an adhesive solution by dissolving them in a solvent. Battery packaging materials are manufactured by a dry lamination method in which an adhesive solution is applied to an aluminum foil or a film for a sealant layer, dried, and then the aluminum foil and the film for a sealant layer are laminated together. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2010-92703 A [Patent Document 2] JP 2014-89985 A Summary of the Invention [Problem to be solved by the invention]
[0006] The adhesives described in Patent Documents 1 and 2 have a problem in that the acid-modified polyolefin and the polyfunctional isocyanate compound start to react and thicken early after mixing. For this reason, they need to be mixed just before applying the adhesive solution, which makes it difficult to manufacture battery packaging materials on an industrial scale. An object of one embodiment of the present invention is to provide an adhesive composition having a long pot life and an acid-modified polyolefin solution serving as a raw material therefor. [Means for solving the problem]
[0007] As a result of intensive research by the present inventors to solve the above problems, they have completed the following invention. Based on these findings, the present specification provides the following means.
[0008] <1> An acid-modified polyolefin solution comprising an acid-modified polyolefin and an organic solvent, the solution having a water content of 1100 ppm by weight or less. <2> The weight of water in the solution is 20 ppm or more. <1> The acid-modified polyolefin solution according to claim 1. <3> It is an adhesive raw material. <1> or <2> The acid-modified polyolefin solution according to claim 1. <4> The acid-modified polyolefin contains an acid anhydride structure. <1> ~ <3> 2. The acid-modified polyolefin solution according to claim 1 . <5> The acid-modified polyolefin contains a cyclic acid anhydride structure. <1> ~ <4> 2. The acid-modified polyolefin solution according to claim 1 . <6> A two-component curing adhesive composition comprising a first agent and a second agent, The first agent <1> ~ <4> 2. An adhesive composition comprising the acid-modified polyolefin solution according to claim 1, wherein the second agent contains a polyfunctional isocyanate compound. <7> <6> A cured product of the adhesive composition described above. <8> <6> 1. A heat-fusible member comprising an adhesive layer formed by curing the adhesive composition described in claim 1, a metal layer bonded to one side of the adhesive layer, and a heat-fusible resin layer bonded to the other side of the adhesive layer. <9> <8> A packaging material for an electricity storage device, comprising the heat-sealable member according to claim 1.
[0009] According to the present invention, an adhesive composition having a long pot life can be obtained. [Brief description of the drawings]
[0010] [Figure 1] 1 is a schematic perspective view illustrating an example of a heat-fusible member of the present invention. [Diagram 2] FIG. 2 is a schematic perspective view showing another example of the heat-fusible member of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In the present disclosure, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits. In the present disclosure, when a plurality of substances corresponding to each component are present in the composition, the amount of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified. In the numerical ranges described in stages in this disclosure, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In the numerical ranges described in this disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples.
[0012] Hereinafter, the adhesive composition of the present invention will be described in detail with respect to each of its constituent components. 1. Acid-modified polyolefin The acid-modified polyolefin is a polyolefin having a carboxy group and / or a carboxylic anhydride group, and is preferably a polyolefin modified with a carboxy group-containing monomer and / or a carboxylic anhydride group-containing monomer.
[0013] The modification method may be a known method, such as graft modification in which a carboxyl group-containing monomer and / or a carboxylic anhydride group-containing monomer is added to a polyolefin in the presence of a known radical polymerization initiator such as an organic peroxide or an aliphatic azo compound in melt kneading or in an organic solvent, and copolymerization of a carboxyl group-containing monomer and / or a carboxylic anhydride group-containing monomer with an olefin.
[0014] Among these methods, it is preferable to produce an acid-modified polyolefin by acid-modifying a polyolefin capable of radical graft reaction with an unsaturated carboxylic acid anhydride. A polyolefin capable of radical graft reaction is a polyolefin containing a monomer unit having a hydrogen atom that can be abstracted by a radical. A polyolefin capable of radical graft reaction is usually a polyolefin that is not acid-modified (i.e., a polyolefin that does not contain a carboxy group or an acid anhydride structure), but may be partially acid-modified, such as at the terminal portion, in some cases. In this specification, this polyolefin capable of radical graft reaction may also be referred to as "polyolefin before acid modification."
[0015] Specific examples of polyolefins capable of radical graft reaction include those obtained by homopolymerization or copolymerization of polymerizable monomers selected from the group consisting of olefins (preferably having 2 to 6 carbon atoms, more preferably having 2 to 4 carbon atoms), styrene, cycloolefins (preferably having 3 to 10 carbon atoms, more preferably having 5 to 8 carbon atoms), and combinations thereof. In particular, polyolefins obtained from polymerizable monomers that generate relatively stable tertiary carbon radicals are preferred, and among these, copolymers of propylene and 1-butene have good solubility in solvents such as toluene and cyclohexane, and also have high adhesive performance, making them suitable for use as solution-type adhesives.
[0016] In the copolymer of propylene and 1-butene, the copolymerization ratio of 1-butene [1-butene / (propylene+1-butene)] is preferably 5-40 mol%, more preferably 10-30 mol%. If the copolymerization ratio of 1-butene is less than 5 mol%, the solubility in the solvent is insufficient, and even if the polyolefin is dissolved in the solvent by heating, the fluidity of the polyolefin solution is lost in a short time, and the adhesive may not be able to be applied. If the copolymerization ratio of 1-butene exceeds 40 mol%, the hot adhesion properties are reduced.
[0017] The melting point of the radically graft-reactive polyolefin is preferably 44°C or higher, more preferably 54°C or higher, particularly preferably 64°C or higher, and may be 74°C or higher. Within such a range, the adhesive composition can obtain sufficient peel strength. The melting point of the radically graft-reactive polyolefin is preferably 125°C or lower, more preferably 120°C or lower, particularly preferably 105°C or lower, and may be 95°C or lower. Within such a range, sufficient storage stability at low temperatures can be obtained.
[0018] The unsaturated carboxylic anhydride is a carboxylic anhydride having at least one carbon-carbon double bond. The number of carbon atoms in the unsaturated carboxylic anhydride is usually 4 or more, and may be, for example, 5 or more or 6 or more. The upper limit of the number of carbon atoms in the unsaturated carboxylic anhydride is not particularly limited, but the number of carbon atoms in the unsaturated carboxylic anhydride may be, for example, 10 or less or 8 or less.
[0019] Examples of the unsaturated carboxylic acid anhydride include acid anhydrides of unsaturated dicarboxylic acid compounds such as maleic anhydride, itaconic anhydride, citraconic anhydride, tetrahydrophthalic anhydride, nadic anhydride, and endic anhydride; and acid anhydrides of unsaturated tricarboxylic acid compounds such as aconitic anhydride. In particular, acid anhydrides having an acid anhydride structure and a five-membered ring consisting of a carbon-carbon bond are preferred. Such a five-membered ring is also called an "acid anhydride ring."
[0020] As the unsaturated carboxylic acid anhydride, an unsaturated dicarboxylic acid anhydride is preferred from the viewpoints of ease of modification and excellent adhesiveness, and specifically, maleic anhydride and itaconic anhydride are preferred.
[0021] These unsaturated carboxylic acid anhydrides may be used alone or in combination of two or more.
[0022] In the acid-modified polyolefin, a part of the acid anhydride structure derived from the unsaturated carboxylic acid anhydride (for example, more than 0 mol % to 30 mol % or 5 mol % to 20 mol %) may be hydrolyzed to a carboxylic acid. However, in order to extend the pot life, it is preferable that the acid anhydride structure is maintained. In the acid-modified polyolefin, the ring opening rate of the acid anhydride ring is preferably 20% or less, more preferably 10% or less, and particularly preferably 5% or less.
[0023] The degree of opening of the acid anhydride ring can be calculated by the following procedure. Wave number 1786cm -1 The absorbance of the acid-modified polyolefin was normalized based on the absorption peak at a wavenumber where the absorption does not increase or decrease depending on the ring-opening state of the acid anhydride group, and the ring-opening rate was estimated by comparing the height of the normalized absorption peak derived from the acid anhydride. In this calculation, the infrared absorption spectrum of the acid-modified polyolefin ring-closed by vacuum drying at 150 °C for 2 hours has a peak at 1710 cm -1 Since the absorption peak of the carboxyl group in the vicinity was no longer observed, the opening rate of the acid anhydride ring in this state was determined to be 0%. In addition, the absorption peak at wavenumber 1164 cm, which is the standard not affected by the acid anhydride group or moisture, was -1 was calculated as the peak. <Calculation formula> In the infrared absorption spectrum of the product dried in vacuum at 150°C for 2 hours, -1 The absorbance of the absorption peak is set to 1, and the normalized wave number is 1786 cm -1 The normalized absorbance of the peak is defined as X. That is, X is calculated by the following formula: Dry polymer 1786cm -1 Measured absorbance of dry polymer at 1164 cm -1 Measured absorbance = X In the infrared absorption spectrum of an acid-modified polymer in which the acid anhydride ring has been partially opened due to moisture absorption, the normalized wave number is 1786 cm -1 The peak height of is defined as Y. That is, Y is calculated by the following formula. Ring-opened polymer: 1786cm -1 Measured absorbance of the ring-opened polymer at 1164 cm -1 Measured absorbance = Y From the normalized absorbances X and Y, the ring opening rate is calculated as follows: Ring opening rate [%]=(XY) / X×100
[0024] The amount of grafted unsaturated carboxylic acid anhydride in the acid-modified polyolefin can be confirmed by the amount of acid anhydride structure (-CO-O-CO-) present in the acid-modified polyolefin. The amount of acid anhydride structure is evaluated by the acid value. The acid value of the acid-modified polyolefin is preferably 1 mgKOH / g or more, more preferably 5 mgKOH / g or more, and even more preferably 10 mgKOH / g or more. When the acid value of the acid-modified polyolefin is within any of these ranges, high adhesive strength is obtained. The acid value of the acid-modified polyolefin is preferably 60 mgKOH / g or less, more preferably 50 mgKOH / g or less, and even more preferably 40 mgKOH / g or less. When the acid value of the acid-modified polyolefin is within any of these ranges, the stability of the adhesive solution is improved.
[0025] The acid-modified polyolefin may be further graft-modified with an alkyl (meth)acrylate ester. However, in one embodiment of the present invention, it may be preferable that the acid-modified polyolefin is not graft-modified with an alkyl (meth)acrylate ester. As the alkyl (meth)acrylate ester, an ester compound of an alkyl alcohol having 8 to 18 carbon atoms and (meth)acrylic acid (hereinafter referred to as "long-chain alkyl (meth)acrylate ester" is preferable. The order in which the unsaturated carboxylic anhydride and the alkyl (meth)acrylate ester are grafted onto the polyolefin before acid modification is not particularly limited, and they may be graft-modified simultaneously or separately.
[0026] The melting point of the acid-modified polyolefin is preferably 40°C or higher, more preferably 50°C or higher, particularly preferably 60°C or higher, and may be 70°C or higher. In such a range, the adhesive composition can obtain sufficient peel strength. The melting point of the acid-modified polyolefin is preferably 90°C or lower, more preferably 85°C or lower, particularly preferably 80°C or lower. When the melting point is within this range, it becomes possible to laminate the adhesive composition at a low temperature, and the thermal expansion of the adherend can be suppressed. The melting point can be measured at a heating rate of 10°C / min using a differential scanning calorimeter (DSC) in accordance with JIS K7121.
[0027] The melt flow rate of the acid-modified polyolefin is preferably 50 g / 10 min or more, more preferably 100 g / 10 min or more. The melt flow rate of the acid-modified polyolefin is preferably 1000 g / 10 min or less, more preferably 800 g / 10 min or less. By setting the melt flow rate to 50 g / 10 min or more, the solution viscosity of the adhesive composition is reduced, and the coating speed can be improved. On the other hand, by setting the melt flow rate to 1000 g / 10 min or less, the hot peel strength can be further improved. The melt flow rate can be measured in accordance with JIS K7210 at a test temperature of 190° C. and a test load of 2.17 kg.
[0028] The weight average molecular weight of the acid-modified polyolefin may be, for example, within the range of 15,000 to 200,000. In terms of improving peel strength and electrolyte resistance, the weight average molecular weight of the acid-modified polyolefin is preferably 15,000 or more, more preferably 30,000 or more. In terms of improving solubility in organic solvents, the weight average molecular weight of the acid-modified polyolefin is preferably 200,000 or less, more preferably 150,000 or less, and particularly preferably 100,000 or less. The weight average molecular weight is a value obtained by converting the molecular weight measured by gel permeation chromatography into polystyrene equivalent.
[0029] The content of the acid-modified polyolefin in the adhesive composition is preferably 50 to 95 wt %, and more preferably 60 to 90 wt %, relative to 100 wt % of the solid content of the adhesive composition, in order to achieve excellent hot peel strength and electrolyte resistance.
[0030] The radical graft reaction method of the acid-modified polyolefin is classified into two types of methods. One is a method (thermal melting method) in which other reactive components are mixed into a thermally melted polyolefin capable of radical graft reaction and reacted. The other is a method (solution method) in which a solvent is used to mix and dissolve reactive components including a polyolefin capable of radical graft reaction in the solvent and react them. In the present embodiment, acid-modified polyolefins produced by either method can be preferably used.
[0031] When a portion of the unsaturated carboxylic acid anhydride used in the acid modification remains unreacted, it may be removed, if necessary, by a known method such as distillation by heating and purification by reprecipitation.
[0032] 2. Polyfunctional isocyanate compounds The adhesive composition contains a polyfunctional isocyanate compound. The polyfunctional isocyanate compound is a compound having two or more isocyanate groups and is capable of crosslinking the acid-modified polyolefin.
[0033] The polyfunctional isocyanate compound is not particularly limited, and various polyfunctional isocyanate compounds of aromatic, aliphatic, and alicyclic types can be used. Examples of the polyfunctional isocyanate compound include pentamethylene diisocyanate, hexamethylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, and norbornane diisocyanate.
[0034] In this specification, the term "polyfunctional isocyanate compound" includes not only polyfunctional isocyanate compounds, but also derivatives formed from polyfunctional isocyanate compounds. Derivatives of polyfunctional isocyanate compounds are compounds in which an isocyanate group is changed to an isocyanurate bond, a biuret bond, a urethane bond, an allophanate bond, a urea bond, or a uretdione bond by a chemical reaction. Compounds containing an isocyanurate bond are particularly preferred in that they are highly effective in improving adhesion to an adherend and can improve room temperature peel strength and electrolyte resistance. The derivative is a derivative in which at least two isocyanate groups remain unreacted.
[0035] The derivative may be formed from two or more of the same or different polyfunctional isocyanate compounds. Specific examples of such derivatives of polyfunctional isocyanate compounds include multimers of polyfunctional isocyanate compounds. Multimers of polyfunctional isocyanate compounds may be formed through the above-mentioned bonds such as uretdione bonds, isocyanurate bonds, and allophanate bonds. The polyfunctional isocyanate compounds forming the multimer are usually all the same type of polyfunctional isocyanate compounds, but may be different types of polyfunctional isocyanate compounds. The number of polyfunctional isocyanate compounds constituting the multimer is not particularly limited, and may be a multimer of a general isocyanate compound. Specifically, the multimer may be a dimer, trimer, tetramer, or the like.
[0036] In this specification, when a polyfunctional isocyanate compound is a derivative formed from different types of polyfunctional isocyanate compounds, the derivative is described as a derivative of any of the different types of polyfunctional isocyanate compounds. For example, a derivative formed from two different types of polyfunctional isocyanate compounds, that is, a polyfunctional isocyanate compound (A) and a polyfunctional isocyanate compound (B), is both a derivative of the polyfunctional isocyanate compound (A) and a derivative of the polyfunctional isocyanate compound (B).
[0037] In one embodiment of the present invention, the adhesive composition may contain two or more, particularly two, polyfunctional isocyanate compounds. By containing two or more polyfunctional isocyanate compounds, hot peel strength and electrolyte resistance can be improved.
[0038] Here, the two types of polyfunctional isocyanate compounds are described as polyfunctional isocyanate compound (1) and polyfunctional isocyanate compound (2). The polyfunctional isocyanate compound (1) and the polyfunctional isocyanate compound (2) are different compounds. One or both of the polyfunctional isocyanate compound (1) and the polyfunctional isocyanate compound (2) may be derivatives. When the adhesive composition contains a derivative of a polyfunctional isocyanate compound, the polyfunctional isocyanate compound (1) and the polyfunctional isocyanate compound (2) may form one derivative, but it is preferable that the polyfunctional isocyanate compound (1) and the polyfunctional isocyanate compound (2) each independently form one derivative.
[0039] In one embodiment of the present invention, the polyfunctional isocyanate compound (1) may be a polyfunctional isocyanate compound having a hydrocarbon group having 4 to 7 carbon atoms, particularly a diisocyanate compound, and the polyfunctional isocyanate compound (2) may be a polyfunctional isocyanate compound having a hydrocarbon group having 8 to 14 carbon atoms, particularly a diisocyanate compound.
[0040] In one embodiment of the present invention, the polyfunctional isocyanate compound (1) may be a polyfunctional isocyanate compound having an aliphatic hydrocarbon group, particularly a diisocyanate compound, and the polyfunctional isocyanate compound (2) may be a polyfunctional isocyanate compound having an alicyclic hydrocarbon group, particularly a diisocyanate compound. The number of carbon atoms in the aliphatic hydrocarbon group may be, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10. The alicyclic hydrocarbon group is a hydrocarbon group containing an aliphatic ring, and the aliphatic ring may be linked to an aliphatic hydrocarbon group having, for example, 1 to 3 carbon atoms. As the aliphatic ring, a cyclohexane ring, a cyclopentane ring, or the like can be preferably used. The number of carbon atoms in the aliphatic ring may be, for example, 4, 5, 6, 7, 8, 9, or 10.
[0041] The weight ratio of the polyfunctional isocyanate compound (1) to the polyfunctional isocyanate compound (2) (polyfunctional isocyanate compound (1) / polyfunctional isocyanate compound (2)) is not particularly limited. In one embodiment, the weight ratio of the polyfunctional isocyanate compound (1) to the polyfunctional isocyanate compound (2) (polyfunctional isocyanate compound (1) / polyfunctional isocyanate compound (2)) is preferably in the range of 1 / 3 to 3 / 1, more preferably in the range of 1 / 2 to 2 / 1, and the weight of the polyfunctional isocyanate compound (1) and the weight of the polyfunctional isocyanate compound (2) may be the same.
[0042] Specific examples of the polyfunctional isocyanate compound having a hydrocarbon group having 4 to 7 carbon atoms include hexamethylene diisocyanate, pentamethylene diisocyanate, and tetramethylene diisocyanate.
[0043] As the derivative of the polyfunctional isocyanate compound having a hydrocarbon group having 4 to 7 carbon atoms, a commercially available product can be used. Commercially available compounds having an isocyanurate bond include Duranate TPA-100 (manufactured by Asahi Kasei Corporation), Duranate MFA-75B (manufactured by Asahi Kasei Corporation), Duranate TUL-100 (manufactured by Asahi Kasei Corporation), Duranate TSA-100 (manufactured by Asahi Kasei Corporation), Coronate HX (manufactured by Tosoh Corporation), and Takenate D-170N (manufactured by Mitsui Chemicals, Inc.). Commercially available compounds having a burette bond include Duranate 24A-100 (manufactured by Asahi Kasei Corporation), Duranate 21S-75E (manufactured by Asahi Kasei Corporation), Takenate D-165NN (manufactured by Mitsui Chemicals, Inc.), and Desmodur N3200 (manufactured by Sumika Covestro Urethane Co., Ltd.). Commercially available compounds having a urethane bond include Duranate P301-75E (manufactured by Asahi Kasei Corp.), which is an adduct of hexamethylene diisocyanate and trimethylolpropane, and Sumidur HT (manufactured by Sumika Covestro Urethane Corp.). Commercially available products of compounds having an allophanate bond include Desmodur XP2580 (manufactured by Sumika Covestro Urethane Co., Ltd.).
[0044] Specific examples of polyfunctional isocyanate compounds having a hydrocarbon group having 8 to 14 carbon atoms include polyfunctional isocyanate compounds having one secondary isocyanate group, such as isophorone diisocyanate and norbornane diisocyanate, polyfunctional isocyanate compounds having two secondary isocyanate groups, such as 4,4'-methylenebis(cyclohexyl isocyanate), and polyfunctional isocyanate compounds having no secondary isocyanate groups, such as dodecane diisocyanate and 1,3-bis(isocyanatomethyl)cyclohexane.
[0045] As the derivative of the polyfunctional isocyanate compound having a hydrocarbon group having 8 to 14 carbon atoms, a commercially available product can be used. Commercially available compounds having an isocyanurate bond include Desmodur Z4470 BA (manufactured by Sumika Covestro Urethane Co., Ltd.) and Duranate T4900-70B (manufactured by Asahi Kasei Corporation). Commercially available products of compounds having an allophanate bond include Desmodur XP2565 (manufactured by Sumika Covestro Urethane Co., Ltd.). Commercially available compounds having a urethane bond include Takenate D-140N (manufactured by Mitsui Chemicals, Inc.), which is an adduct of isophorone diisocyanate and trimethylolpropane, and VESTANAT EP-DC1241 (manufactured by Evonik Japan Co., Ltd.), which is a monoadduct of isophorone diisocyanate and hydroxyethyl acrylate.
[0046] The amount of the polyfunctional isocyanate compound in the adhesive composition can be determined from the ratio (NCO / COOH) of the number of moles of isocyanate groups in the polyfunctional isocyanate compound to the number of moles of carboxy groups in the acid-modified polyolefin. The number of moles of carboxy groups in the acid-modified polyolefin is the number of moles of carboxy groups when each of the acid anhydride structures (-CO-O-CO-) present in the acid-modified polyolefin is considered as two carboxy groups. In order to improve the hot peel strength of the adhesive composition, the ratio of the number of moles of isocyanate groups in the polyfunctional isocyanate compound to the number of moles of carboxy groups in the acid-modified polyolefin is preferably 1 or more, more preferably 2 or more, and may be 10 or more. In order to improve the adhesive strength with metals such as aluminum, particularly the hot peel strength, the ratio of the number of moles of isocyanate groups in the polyfunctional isocyanate compound to the number of moles of carboxy groups in the acid-modified polyolefin is preferably 20 or less, more preferably 15 or less. The number of moles of carboxy groups can be calculated based on the acid value measurement method described in the examples below.
[0047] The amount of the polyfunctional isocyanate compound in the adhesive composition can also be determined by the weight ratio of the polyfunctional isocyanate compound to the total weight of the acid-modified polyolefin and the polyfunctional isocyanate compound (hereinafter, also referred to as the polyfunctional isocyanate compound content). The polyfunctional isocyanate compound content is preferably 5% by weight or more, more preferably 10% by weight or more, and particularly preferably 20% by weight or more. The polyfunctional isocyanate compound content is preferably 60% by weight or less, more preferably 40% by weight or less.
[0048] 3. Solvent The adhesive composition contains an organic solvent that dissolves the acid-modified polyolefin. Specific examples of the organic solvent include aromatic organic solvents such as toluene and xylene, aliphatic organic solvents such as n-hexane, alicyclic organic solvents such as cyclohexane, methylcyclohexane, and ethylcyclohexane, ketone organic solvents such as acetone and methyl ethyl ketone, alcohol organic solvents such as methanol and ethanol, ester organic solvents such as ethyl acetate and butyl acetate, and propylene glycol ether organic solvents such as propylene glycol methyl ether, propylene glycol ethyl ether, and propylene glycol-t-butyl ether.
[0049] In the adhesive composition of the present invention, the organic solvent may be used alone or in combination of two or more kinds.
[0050] Among these, the organic solvent is preferably a mixed solvent containing an alicyclic organic solvent and a ketone organic solvent. The mixed solvent of an alicyclic organic solvent and a ketone organic solvent can dissolve the polyfunctional isocyanate compound appropriately and improve the hot peel strength of the cured product of the adhesive composition of the present invention. The total content of the alicyclic organic solvent and the ketone organic solvent in the mixed solvent is preferably 80% by weight or more, more preferably 90% by weight or more, and may be 100% by weight. The weight ratio of the alicyclic organic solvent and the ketone organic solvent in the mixed solvent (weight of the alicyclic organic solvent / weight of the ketone organic solvent) is preferably 8 / 2 or less, more preferably 7 / 3 or less, and particularly preferably 6 / 4 or less. The weight ratio of the alicyclic organic solvent and the ketone organic solvent in the mixed solvent (weight of the alicyclic organic solvent / weight of the ketone organic solvent) is preferably 2 / 8 or more, more preferably 3 / 7 or more, and particularly preferably 5 / 5 or more.
[0051] The amount of the solvent in the adhesive composition and the acid-modified polyolefin solution described later is not particularly limited and may be appropriately determined depending on the type of acid-modified polyolefin. In the adhesive composition and the acid-modified polyolefin solution, when the total amount of the acid-modified polyolefin and the solvent is 100% by weight, the amount of the acid-modified polyolefin is preferably 5 to 25% by weight, more preferably 10 to 20% by weight. If the solvent is present in the adhesive composition or the acid-modified polyolefin solution in such a content, the adhesive composition can be easily applied to the adherend, and the workability is excellent.
[0052] 4. Additional Ingredients The adhesive composition may further contain additional components depending on the purpose, such as a curing catalyst, a thermoplastic resin, a tackifier, an antioxidant, a hindered amine light stabilizer, an ultraviolet absorber, an antistatic agent, a flame retardant, a colorant, a dispersant, an adhesion imparting agent, an antifoaming agent, a leveling agent, a plasticizer, a lubricant, a crystal nucleating agent, and a filler.
[0053] These components are described below. The additional components are optional components and may not be used, or only one type may be used, or two or more types may be used in combination.
[0054] The curing catalyst can be blended for the purpose of promoting the crosslinking reaction between the acid-modified polyolefin and the polyfunctional isocyanate compound and obtaining excellent adhesive performance. As the curing catalyst, tertiary amines, metal carboxylates, complex salts, organic metals, etc. are preferable.
[0055] Specific examples of tertiary amines include tetraalkylethylenediamines such as tetramethylethylenediamine; N,N'-dialkylbenzylamines such as dimethylbenzylamine; triethylenediamine, pentamethyldiethylenetriamine, N-ethylmorpholine, N-methylmorpholine, 1-methyl-4-dimethylamineethylpiperazine, and 1,8-diazabicyclo[5.4.0]undecene-7.
[0056] Examples of metal carboxylates and complex salts include metal acetates, metal hexanoates, metal octanoates such as metal 2-ethylhexanoates, metal neodecanoates, metal laurates, metal stearates, metal oleates, and metal complex salts such as metal acetylacetonates. The organic metal is not particularly limited as long as it is a metal compound having a bond with carbon, and examples thereof include organic metal oxides. The metal is preferably one or more metals selected from the group consisting of metals in Groups 7, 12, and 14 of the periodic table. These may be used alone or in combination of two or more. Among these, from the viewpoint of adhesion when the adhesive layer formed by the adhesive composition of the present invention is in contact with an electrolyte, carboxylates, acetylacetonates, and organic metals of any of tin, zinc, and manganese are more preferable. Specific examples include zinc neodecanoate, dibutyltin dilaurate, dioctyltin dilaurate, dioctyltin diacetate, dibutyltin maleate, dibutyltin oxide, dioctyltin oxide, zinc bis(neodecanoate), zinc bis(2-ethylhexanoate), zinc distearate, zinc(II) acetylacetonate, manganese bis(2-ethylhexanoate), etc. Among these, dibutyltin dilaurate, dioctyltin dilaurate, and dioctyltin oxide are more preferred from the viewpoint of the balance of adhesion, electrolyte resistance, and heat resistance of the adhesive layer.
[0057] As the curing catalyst, an organotin compound and a tertiary amine can also be used in combination.
[0058] The content of the curing catalyst is preferably 0.001 to 5 parts by weight per 100 parts by weight of the total amount of the acid-modified polyolefin and the polyfunctional isocyanate compound. By setting the content of the curing catalyst to 0.001 part by weight or more, it is easy to obtain a sufficient catalytic effect, and by setting the content of the curing catalyst to 5 parts by weight or less, the storage stability of the adhesive composition can be ensured.
[0059] A thermoplastic resin such as a styrene-based thermoplastic elastomer can be blended into the adhesive composition for the purpose of improving adhesive strength. In one embodiment of the present invention, the adhesive composition does not need to contain any thermoplastic resin other than the acid-modified polyolefin.
[0060] Specific examples of styrene-based thermoplastic elastomers include styrene-based resins such as styrene-butadiene copolymer, epoxy-modified styrene-butadiene copolymer, styrene-butadiene-styrene block copolymer, styrene-ethylene / propylene-styrene block copolymer (hereinafter referred to as "SEPS"), styrene-ethylene / butylene-styrene block copolymer (hereinafter referred to as "SEBS"), styrene-isoprene / butadiene-styrene block copolymer, and styrene-isoprene-styrene block copolymer, and these may be ones that do not have acidic groups and acid anhydride groups, or ones that have acidic groups and / or acid anhydride groups, or ones that have amino groups.
[0061] As the tackifier, known ones can be used, and examples thereof include polyterpene resins, rosin resins, aliphatic petroleum resins, alicyclic petroleum resins, copolymer petroleum resins, and hydrogenated petroleum resins.
[0062] The content of the tackifier is preferably 1 to 20% by weight, and more preferably 1 to 10% by weight, relative to 100% by weight of the adhesive composition, in that excellent hot water resistance is achieved.
[0063] 5. Adhesive Composition The adhesive composition can be produced by a known method. Specifically, the method is a method of mixing an acid-modified polyolefin solution (also described as the first agent) containing an acid-modified polyolefin and an organic solvent with a polyfunctional isocyanate compound (also described as the second agent). That is, the adhesive composition is a two-liquid curing adhesive containing a first agent and a second agent. In this method, components other than the acid-modified polyolefin and the polyfunctional isocyanate compound may be added to either the first agent or the second agent. Here, the acid-modified polyolefin solution may be in a slurry state with some components not dissolved. In the present disclosure, the "solution" includes both the complete solution described above and the solution with some components not dissolved. The temperature during mixing is usually 40°C or less, preferably 10°C to 30°C. In this embodiment, the usable time of the adhesive composition can be longer than in the past, and the time from mixing the first agent and the second agent to application does not necessarily need to be shorter. For example, a period of about one day to one week may be allowed between mixing and application.
[0064] Each component of the adhesive composition contains a small amount of water as an impurity. In particular, acid-modified polyolefin and organic solvents are prone to moisture absorption, and simply mixing each component results in an acid-modified polyolefin solution containing about 1200 ppm or more of moisture. In order to obtain an acid-modified polyolefin solution with a low moisture content, it is preferable to dry each component before mixing. The moisture content of the organic solvent can be reduced by removing moisture with a molecular sieve. The moisture content in the organic solvent is preferably 1000 ppm or less, more preferably 700 ppm or less, and may be 100 ppm or less, based on the total weight of the organic solvent. In addition, the moisture content of the acid-modified polyolefin can be reduced by storing it together with a moisture absorbent such as silica gel or drying it under reduced pressure.
[0065] The water content in the acid-modified polyolefin solution is 1100 ppm or less based on the total weight of the acid-modified polyolefin solution. When the water content in the acid-modified polyolefin solution is 1100 ppm or less, the reactivity of the polyfunctional isocyanate compound is reduced during preparation of the adhesive composition, and early thickening of the adhesive composition can be prevented. Furthermore, the peel strength of the packaging material for the electric storage device obtained by maintaining the adhesive composition at an appropriate viscosity can be improved. From the viewpoint of preventing early thickening, the water content in the acid-modified polyolefin solution is preferably 800 ppm or less, more preferably 500 ppm or less. The water content in the acid-modified polyolefin solution is preferably 10 ppm or more based on the total weight of the acid-modified polyolefin solution. By making the water content in the acid-modified polyolefin solution 10 ppm or more, the reactivity of the polyfunctional isocyanate can be prevented from being excessively decreased, and the adhesive composition can be sufficiently cured. From the viewpoint of improving the peel strength, the water content in the acid-modified polyolefin solution is preferably 20 ppm or more, more preferably 30 ppm or more. The water content in the acid-modified polyolefin solution is measured by the method described in the following Examples. The water content in the acid-modified polyolefin solution is calculated according to the following formula. Water content (ppm) = water weight (μg) / acid-modified polyolefin solution weight (g)
[0066] 6.Heat-sealing materials The adhesive composition can be used to produce a heat-sealable member. The heat-sealable member includes an adhesive layer formed by curing the adhesive composition of the present invention, a metal layer bonded to one side of the adhesive layer, and a heat-sealable resin layer bonded to the other side of the adhesive layer.
[0067] Schematic diagrams of heat-sealing members are shown in Figures 1 and 2. That is, the heat-sealing member 1 in Figure 1 sequentially comprises a heat-sealing resin layer 11, an adhesive layer 12, and a metal layer 13. Also, the heat-sealing member 1 in Figure 2 sequentially comprises a heat-sealing resin layer 11, an adhesive layer 12, a metal layer 13, and another layer 14.
[0068] The shape of the heat-sealable member may be appropriately determined depending on the application, etc., and is not particularly limited, but examples thereof include a film, a sheet, a plate, etc.
[0069] The above-mentioned heat-sealable resin layer is a layer containing a resin that can be melted by heat and fuse the material constituting the layer on one side with the material constituting the layer on the other side. The heat-sealable resin layer is preferably a layer containing a resin that melts at a temperature of 50°C to 200°C. Examples of resins having such properties include polyolefin resins, polyamide resins, and polyester resins. Among these, polyolefin resins are preferred because they can be heat-sealed with sufficient strength. Furthermore, polypropylene is preferred as the polyolefin resin. In particular, when the heat-sealable member is used to integrate with other members, unstretched polypropylene is more preferred because there is little dimensional change (shrinkage).
[0070] The above-mentioned heat-fusible resin layer may be a layer containing additives such as a lubricant, a filler, a heat stabilizer, an antioxidant, an ultraviolet absorber, an antistatic agent, a flame retardant, a colorant, a dispersant, and an adhesion imparting agent, as necessary.
[0071] The thickness of the above-mentioned heat-sealable resin layer is not particularly limited depending on the resin material, but for example, in the case of a layer containing unstretched polypropylene, it is preferably 10 to 200 μm, more preferably 20 to 100 μm. If the thickness of the layer containing unstretched polypropylene is 10 to 200 μm, it is possible to obtain a heat-sealed composite product such as a sealed container that is not easily broken and has high durability.
[0072] The adhesive layer is a layer formed by curing the adhesive composition. The thickness of the adhesive layer is not particularly limited, but is preferably 1 to 20 μm, and particularly preferably 2 to 10 μm. If the adhesive layer has a thickness of 1 to 20 μm, the heat-fusible member is easy to process, such as by folding, when the member is in the form of a sheet.
[0073] The metal layer is a layer containing a metal or an alloy. Examples of the metal or alloy include aluminum, iron, titanium, magnesium, copper, nickel, chromium, and other metals, as well as alloys thereof. Among these, aluminum is preferred because of its excellent workability. The thickness of the metal layer is not particularly limited depending on the material and the like. When the metal layer is made of aluminum, for example, it is preferably 20 to 100 μm, particularly preferably 20 to 80 μm, and further preferably 30 to 60 μm.
[0074] When the heat-sealable member includes a metal layer, another layer 14 can be provided on the surface of the metal layer 13 as shown in FIG. 2. The material constituting the other layer preferably includes a resin from the viewpoint of protecting the metal layer. That is, the other layer is preferably a resin layer. This resin is not particularly limited, and can be a polyamide resin, a polyester resin, or the like. The transparency of the resin layer is not particularly limited, but when this resin layer is transparent or translucent, an excellent appearance can be obtained when it is made into a sealed container or the like as a heat-sealed composite product. The other layer may have a multi-layer structure, and may include, for example, an adhesive layer for bonding the resin layer and the metal layer. The adhesive layer in the other layer may be the same as or different from the adhesive layer provided between the heat-sealable resin layer and the metal layer. The thickness of the other layer is not particularly limited, and is preferably 30 to 60 μm, particularly preferably 30 to 50 μm.
[0075] A heat-fusible part using the adhesive composition of the present invention has high hot peel strength and excellent adhesion, and also has excellent resistance to solvents such as electrolytes, so that the contents can be prevented from deteriorating while maintaining their structure.
[0076] When used as a packaging material for lithium-ion batteries, the adhesive performance can be maintained even if there are temperature changes during battery storage or use, and in particular, the adhesive performance can be maintained during the chemical temperature rise of the battery constituent materials accompanying charging or discharging, in temperature ranges higher than normal temperature in summer or inside an automobile, and in temperature ranges lower than the outside air temperature in cold regions.
[0077] 7. Manufacturing method of heat-sealable member The method for producing the heat-fusible member shown in FIG. 1 is as follows. (1) A method in which an adhesive composition is applied to the surface of a metal foil or the like for forming a metal layer 13, then the organic solvent in the composition is removed to form an adhesive layer 12, and then a resin film for forming a heat-fusible resin layer 11 (hereinafter referred to as a "heat-fusible resin film") is brought into contact with the surface on which the adhesive layer 12 is formed, and pressure-bonded while being heated. (2) A method in which an adhesive composition is applied to the surface of a heat-fusible resin film, then the organic solvent in the composition is removed to form an adhesive layer 12, and then a metal foil or the like for forming a metal layer 13 is brought into contact with the surface on which the adhesive layer 12 is formed, and pressure-bonded while being heated.
[0078] The method for producing the heat-fusible member shown in FIG. 2 is as follows. (3) A method in which an adhesive composition is applied to the surface of metal layer 13 in a composite film having a resin layer constituting another layer 14 and a metal layer 13 formed on one side of the resin layer by lamination, vapor deposition, or the like, and then the organic solvent in the composition is removed to form adhesive layer 12, and then the surface on which adhesive layer 12 is formed is brought into contact with a heat-fusible resin film and pressed while being heated. (4) A method in which an adhesive composition is applied to the surface of a heat-fusible resin film, and then the organic solvent in the composition is removed to form an adhesive layer 12, and then the surface on which the adhesive layer 12 is formed is brought into contact with the surface on which the metal layer 13 is formed of a composite film having a resin layer constituting another layer 14 and a metal layer 13 formed on one side of the resin layer by lamination, vapor deposition, or the like, and the resulting film is pressed against the surface on which the adhesive layer 12 is formed while being heated. (5) A method in which a film for forming another layer 14 is extruded onto the surface of the metal layer 13 in the laminate obtained by the above method (1) or (2).
[0079] The adhesive composition is often applied to a material for forming a metal layer such as a metal foil, or to the surface of a metal layer in a composite film having a metal layer and another layer (resin layer), but is not particularly limited. When using a metal foil, it is preferable to use an aluminum foil having a thickness of 20 to 100 μm. This makes it possible to easily form a heat-sealable member in which breakage is suppressed. When using a composite film, it is preferable that the metal layer contains aluminum, and the other layer (resin layer) contains polyamide resin, polyester resin, etc. Furthermore, when manufacturing the heat-sealable member shown in FIG. 2 without using a composite film, that is, when adopting the above method (5), it is preferable to use a film containing polyamide resin, polyester resin, etc. as the film for forming the other layer 14.
[0080] As the heat-sealable resin film, polyolefin resin film, polyamide resin film, polyester resin film, etc. can be used. These resin films can be obtained by film-forming methods such as extrusion, cast molding, T-die, and inflation. The thickness of the heat-sealable resin film is usually 10 to 200 μm. In the present invention, polyolefin resin film is preferred because it can easily perform heat fusion to complete the heat-sealable member and heat fusion when producing a heat-sealed composite product, and non-oriented polypropylene film is particularly preferred because it can obtain a heat-sealed composite product such as a sealed container that is not easily broken and has excellent durability. When using this non-oriented polypropylene film, the preferred thickness is 10 to 200 μm, more preferably 20 to 100 μm.
[0081] The adhesive composition can be applied by a conventional method, for example, by using a bar coater, a gravure coater, etc. The thickness of the coating film and the drying temperature are not particularly limited. The drying temperature of the coating film is not particularly limited, and is preferably 30°C to 150°C from the viewpoint of workability.
[0082] As described above, the dried coating film generally has tackiness and adhesiveness, so that two members can be bonded together without heating, but when producing a heat-sealable member, a method of heating to an appropriate temperature while pressing can be applied, taking into consideration the melting point and melt viscosity of the acid-modified polyolefin, etc. Heating and pressing conditions are, for example, a temperature of 60 to 100°C, a pressure of 0.3 MPa, and a pressing time of 2 seconds.
[0083] The conditions for accelerating the crosslinking reaction between the acid-modified polyolefin and the polyfunctional isocyanate compound to complete the heat-fusible member (hereinafter referred to as "aging conditions") are not particularly limited, and are preferably set according to the material of the metal foil and the material of the heat-fusible resin film, the melting temperature, the composition of the adhesive layer, etc. Examples of the aging conditions include heating at 25 to 80°C, for example 40°C, for about 3 to 7 days.
[0084] 8.Applications The heat-sealable members can be used in a variety of industrial product fields, including electrical, automotive, industrial and other fields.
[0085] Examples of applications in the electrical field include packaging materials for secondary batteries such as lithium-ion batteries and lithium-ion polymer batteries, as well as electricity storage devices such as capacitors, decoration by attaching decorative sheets to mobile devices, television housings, and white goods housings, adhesion between metal members and resins, and sealing of electronic components.
[0086] Applications in the automotive field include bonding of metal / resin exterior materials in interior and exterior components such as pillars, moldings, door trims, spoilers, and roofs, as well as bonding of genuine leather, fabric, instrument panel foam sheets, and decorative sheets to substrates.
[0087] Examples of industrial applications include industrial packaging materials and inter-film bonding in multi-layer films such as barrier films.
[0088] Other examples of applications include adhesion of logistics materials, building materials, daily necessities, and sporting goods.
[0089] Among these, the heat-sealable member is preferably used as a packaging material for an electricity storage device because it has high hot peel strength, excellent adhesiveness, and high resistance to electrolyte. EXAMPLES
[0090] In the tables shown below, the raw materials of the adhesive composition may be represented by abbreviations, and the abbreviations have the following meanings.
[0091] (Acid-modified polyolefin) Acid-modified polyolefin A: an acid-modified polyolefin prepared as follows: In a 1L autoclave, 100 parts by weight of propylene-butene copolymer (Mitsui Chemicals' "Tafmer (registered trademark) XM7070"), 150 parts by weight of toluene, 6 parts by weight of maleic anhydride, and 1 part by weight of di-tert-butyl peroxide were added, and the temperature was raised to 140 ° C., and then the mixture was stirred for 3 hours. After cooling the resulting reaction liquid to 100 ° C., it was poured into a container containing 717 parts by weight of toluene and 950 parts by weight of methyl ethyl ketone, which had been preheated to 40 ° C., while stirring, cooled to 40 ° C., further stirred for 30 minutes, and further cooled to 25 ° C. to precipitate a resin. Thereafter, the slurry containing the resin was centrifuged to separate the acid-modified propylene-butene copolymer, maleic anhydride, and low molecular weight substances. Furthermore, the acid-modified propylene-butene copolymer extracted by centrifugation was poured into a container containing 2,000 parts by weight of methyl ethyl ketone that had been kept at 25°C in advance, while stirring, and the stirring was continued for 1 hour. The slurry was then centrifuged to further separate the acid-modified propylene-butene copolymer from maleic anhydride and low molecular weight substances. This operation was repeated twice for purification. After purification, the product was dried under reduced pressure at 40° C. for 5 hours to obtain acid-modified polyolefin A. The acid-modified polyolefin A obtained had an acid value of 10 mg KOH / g, a melting point of 73° C., and a weight average molecular weight of 91,000.
[0092] Acid-modified polyolefin B: Acid-modified polyolefin produced as follows: Except for changing the raw polyolefin to a propylene-butene copolymer ("TAFMER (registered trademark) XM7080" manufactured by Mitsui Chemicals, Inc.), changing the amount of maleic anhydride to 11 parts by weight, and changing the amount of di-tert-butyl peroxide to 2 parts by weight, the same procedure was followed as for acid-modified polyolefin A to obtain acid-modified polyolefin B. The obtained acid-modified polyolefin B had an acid value of 18 mgKOH / g, a melting point of 70°C, and a weight average molecular weight of 79,000.
[0093] Acid-modified polyolefin C: an acid-modified polyolefin prepared as follows: Into a twin-screw extruder with L / D=42 and φ=58 mm, 1,000 parts by weight of propylene-butene copolymer (Tafmer XM7070 manufactured by Mitsui Chemicals, Inc.), 15 parts by weight of maleic anhydride, 40 parts by weight of lauryl methacrylate, and 15 parts by weight of 2,5-dimethyl-2,5-di(t-butylperoxy)hexane were fed. The reaction was carried out with a residence time of 10 minutes and a barrel temperature of 180°C (1st barrel to 7th barrel), and degassing was carried out in the 7th barrel to remove the remaining unreacted material, thereby obtaining an acid-modified polyolefin C. The obtained acid-modified polyolefin C had an acid value of 13 mgKOH / g, a melting point of 76°C, and a weight average molecular weight of 140,000.
[0094] Acid-modified polyolefin D: an acid-modified polyolefin prepared as follows: Acid-modified polyolefin D was obtained in the same manner as acid-modified polyolefin C, except that the propylene-butene copolymer was changed to Tafmer XM7080 manufactured by Mitsui Chemicals, Inc. The acid-modified polyolefin D obtained had an acid value of 15 mgKOH / g, a melting point of 84°C, and a weight average molecular weight of 150,000.
[0095] [Table 1]
[0096] The acid value, melting point and weight average molecular weight of the acid-modified polyolefins A to D were measured according to the methods described below. (Acid value measurement) (1) 35 g of non-acid-modified resin (propylene butene copolymer) and octadecyl succinic anhydride (no additives, 1 g, 2 g, 4 g) were weighed out and placed in a Labo Plastomill (manufactured by Toyo Seiki Seisakusho Co., Ltd.) heated to 170°C. The mixture was heated and stirred to produce four samples with different octadecyl succinic anhydride contents. (2) A small amount of each sample was cut out, sandwiched between two 1 mm thick fluororesin sheets, and pressed into a film using a hot press at 110°C. This film was vacuum dried at 130°C for 5 hours to close the acid anhydride rings 100%, cooled to room temperature, then sealed in a moisture-proof bag together with a desiccant, and left at room temperature for at least one day before measuring the infrared absorption spectrum using the transmission method. (3) From the transmission IR spectra of the four samples, -1 Absorption (resin-derived peak) at approximately 1799 cm -1 A calibration curve was prepared by plotting the absorbance ratio (peak due to acid anhydride) versus the octadecylsuccinic anhydride content. (4) The acid-modified polyolefins A to D were each vacuum-dried at 130°C for 5 hours to close the acid anhydride rings 100%, cooled to room temperature, and then left in a dry state for at least one day before measuring the infrared absorption spectrum by a transmission method. (5) From the spectrum measured in (4), 1165 cm -1 Absorption of 1799cm -1 The absorbance ratio was calculated and compared with the calibration curve prepared in (3) to measure the acid value.
[0097] (Melt point measurement) The melting point was measured according to JIS K7121 (2012). Specifically, the melting point was determined from the temperature at which the secondary temperature rise in the heat flux curve obtained using a differential scanning calorimeter becomes minimal. The heat flux curve was obtained by cooling approximately 10 mg of the sample to -50°C and holding it for 5 minutes, heating it to 150°C at 10°C / min and holding it for 5 minutes, cooling it to -50°C at 10°C / min and holding it for 5 minutes, heating it to 150°C at 10°C / min and holding it for 5 minutes, then heating it to 150°C at 10°C / min and holding it for 5 minutes, and cooling it to -50°C at 10°C / min. Equipment: DSC6220 manufactured by SII NanoTechnology Co., Ltd. Measurement atmosphere: Nitrogen atmosphere
[0098] (Measurement of weight average molecular weight) The weight average molecular weight of the acid-modified polyolefin was determined in terms of polystyrene using gel permeation chromatography (GPC) using the following apparatus and conditions: Equipment: Tosoh Corporation, model name "HLC-8320" Column: Tosoh Corporation TSKgel-SuperMultipore HZ-M (4.6mmID x 15cm) x 3 Solvent: Tetrahydrofuran Column temperature: 40℃ Detector: RI (Differential Refractive Index Detector) Flow rate: 350μL / min
[0099] (curing catalyst) ·DOTL: Dioctyltin dilaurate
[0100] (Polyfunctional isocyanate compound) TPA-100: Polyisocyanate of hexamethylene diisocyanate, "Duranate TPA-100" manufactured by Asahi Kasei Corporation Z4470 BA: Polyisocyanate of isophorone diisocyanate, "Desmodur Z4470BA" manufactured by Sumika Covestro Urethane Co., Ltd. W: Dicyclohexylmethane-4,4'-diisocyanate, "Desmodur W" manufactured by Sumika Covestro Urethane Co., Ltd.
[0101] <Example 1> (Drying of the solvent) Methylcyclohexane and methyl ethyl ketone were added in a ratio of about 10% by weight of molecular sieves, and the mixture was left to stand for 24 hours. The molecular sieves were then filtered to obtain a dried solvent. The water content in the solvent was measured to be 10 ppm. The water content was measured in the same manner as described below. The dried solvent was used as the solvent for the acid-modified polyolefin solution.
[0102] (Drying of acid-modified polyolefin) The acid-modified polyolefin A was vacuum dried at 150° C. for 2 hours.
[0103] (Preparation of acid-modified polyolefin solution) 15 g of acid-modified polyolefin A and 85 g of a mixed solvent of methylcyclohexane:methyl ethyl ketone = 51:34 (weight ratio) were weighed into a four-neck flask equipped with a cooling tube and a stirring motor, and the flask was immersed in an oil bath under a dry nitrogen stream and heated to 70 °C while stirring until the acid-modified polyolefin A was completely dissolved, and then cooled to room temperature.
[0104] (Measurement of moisture content) The water content of the acid-modified polyolefin solution was measured by Karl Fischer coulometric titration. SIGMA-ALDRICH's Hydranal Coulomat AK (methanol-free) was used as the generating solution, and SIGMA-ALDRICH's Hydranal Coulomat CG-K (methanol-free) was used as the counter solution.
[0105] (Preparation of adhesive solution) To 100g of the acid-modified polyolefin solution, 9g of a polyfunctional isocyanate compound (TPA-100) and 0.18g of dioctyltin dilaurate as a catalyst were added and stirred to prepare an adhesive solution. In the adhesive solution, the ratio of the number of moles of isocyanate groups to the number of moles of carboxyl groups in the acid-modified polyolefin (NCO / COOH) was 10.8.
[0106] (Pot life evaluation) In a 1-liter wide-mouthed plastic bottle, 22.5 g of acid-modified polyolefin was added to a solvent (methylcyclohexane, methyl ethyl ketone), catalyst (dioctyltin dilaurate), and polyfunctional isocyanate compound (TPA-100) in the same ratio as the adhesive solution, and mixed thoroughly. Dehydrated toluene (water content 50 ppm or less) was added to dilute the mixture to a solid content of 13 wt%. A stirrer was placed in the plastic bottle, and the mixture was stirred at 250 rpm without a lid using a magnetic stirrer. The viscosity was measured over time while replenishing the evaporated solvent, and the time from the start until the viscosity increased to over 100 mPa·s was defined as the pot life. A pot life of more than 8 hours was considered to be pass (marked as ◯), and a pot life of less than 8 hours was considered to be fail (marked as ×).
[0107] (Preparation of test pieces for evaluating peel strength) The adhesive solution was applied to a 40 μm thick aluminum foil that had been chemically treated on the adhesive application surface using a bar coater. At this time, the pitch of the bar coater was selected so that the average adhesive thickness after drying would be 2 to 4 μm. In addition, when measuring the peel strength to be performed later, the adhesive was not applied to the part that was clamped by the gripping tool of the tensile tester. This aluminum foil was dried for 1 minute in an oven heated to 80 ° C, and a 80 μm thick CPP (cast polypropylene) film that had been corona discharge treated was superimposed on the surface that contacted the adhesive, and the film was sandwiched and laminated with a roll laminator with a roll temperature of 80 ° C. This was cured for 1 week in a 40 ° C oven to promote the curing reaction, and then cut into 15 mm wide strips to prepare test pieces.
[0108] (Peel strength measurement) Using a thermostatic tensile tester (Shimadzu Corporation Autograph AGS-X), a T-peel test was performed at a pulling speed of 100 mm / min until the test piece gripper moved 100 mm, and the peel strength was calculated by averaging the peel strength from a moving distance of 40 mm to 100 mm. The peel test was performed at room temperature (23°C).
[0109] <Examples 2 to 11> An adhesive solution was prepared in the same manner as in Example 1, using the acid-modified polyolefin, solvent, polyfunctional isocyanate compound, and curing catalyst in the weights shown in Table 1. Note that the solvents used had different water contents. The peel strength and pot life of the obtained adhesive solution were evaluated in the same manner as in Example 1. The water content of the acid-modified polyolefin solution was also measured in the same manner as in Example 1.
[0110] <Comparative Examples 1 to 7> Undried solvent and acid-modified polyolefin were used. The acid-modified polyolefin, solvent, polyfunctional isocyanate compound, and curing catalyst described in Example 1 were used in the weights shown in Table 1 to prepare an adhesive solution in the same manner as in Example 1. The peel strength and pot life of the obtained adhesive solution were evaluated in the same manner as in Example 1. The moisture content of the acid-modified polyolefin solution was also measured in the same manner as in Example 1.
[0111] [Table 2] In the table, NCO / COOH is the molar ratio of carboxyl groups (including carboxyl groups derived from acid anhydrides) to isocyanate groups. The number of moles of carboxyl groups is a value calculated from the acid value.
Claims
1. An acid-modified polyolefin solution comprising an acid-modified polyolefin and an organic solvent, the solution having a water content of 1100 ppm by weight or less.
2. 2. The acid-modified polyolefin solution according to claim 1, wherein the weight of water in the solution is 20 ppm or more.
3. The acid-modified polyolefin solution according to claim 1 or 2, which is a raw material for an adhesive.
4. The acid-modified polyolefin solution according to claim 1 , wherein the acid-modified polyolefin comprises an acid anhydride structure.
5. The acid-modified polyolefin solution according to claim 5 , wherein the acid-modified polyolefin contains a cyclic acid anhydride structure.
6. A two-component curing adhesive composition comprising a first agent and a second agent, 3. An adhesive composition, wherein the first part is the acid-modified polyolefin solution according to claim 1 or 2, and the second part contains a polyfunctional isocyanate compound.
7. A cured product of the adhesive composition according to claim 6.
8. A heat-fusible member comprising an adhesive layer formed by curing the adhesive composition according to claim 6, a metal layer bonded to one side of the adhesive layer, and a heat-fusible resin layer bonded to the other side of the adhesive layer.
9. A packaging material for an electricity storage device, comprising the heat-sealable member according to claim 8 .
Citation Information
Patent Citations
Packaging material for battery case, and case for battery
JP2010092703A
Packaging material for battery case and battery case
JP2014089985A